Adulticidal activity against houseflies (Musca domestica L.; Muscidae: Diptera) of combinations of Cymbopogoncitratus and Eucalyptus globulus essential oils and their major constituents - Moungthipmalai, T.; Soonwera, M. (My University, 2023)
The efficacies of Cymbopogon citratus, Eucalyptus globulus, eucalyptol, geranial, and their combined formulations against houseflies (Musca domestica) were evaluated and compared to cypermethrin, a common synthetic insecticide. Using a standard susceptibility assay that the World Health Organization (WHO) advises, the knockdown and mortality rates were calculated. The tested concentration range of these essential oils and their constituents was between 1% to 5%. The highest efficacy (100% knockdown rate and mortality rate) were provided by a combined formulation of 2% E. globulus EO + 1% geranial. This formulation had a KT50 of 4.27 min. The two next best formulations were 2% C. citratus EO + 1% eucalyptol that provided a KT50 of 5.85 min and an individual 5% C. citratus EO that provided a KT50 of 6.69 min. Most importantly, several tested formulations provided a higher knockdown rate than 1% cypermethrin. Therefore, these formulations have a full potential as an alternative natural insecticide to replace cypermethrin.
Keywords: Cymbopogon citratus; Eucalyptol; Eucalyptus globulus; Geranial; Musca domestica